Enhanced mechanical properties of poly(L‐lactide) braided stent with six‐arm poly(L‐lactide‐co‐ε‐caprolactone) coating cross‐linked by hexamethylene diisocyanate. (16th March 2022) - Deng, Dongwen; Tian, Yuan; Liu, Muqing; Cheng, Jie; Wu, Gensheng; Zhang, Yi; Zhao, Gutian; Ni, Zhonghua
Abstract: Compared with traditional metal stents, biodegradable polymer stents have better biocompatibility but poorer mechanical properties in the treatment of vascular stenosis. It is necessary to improve the mechanical properties of biodegradable polymer stents for further application. For this purpose, we prepared a poly(L‐lactide) braided stent covered with six‐arm poly(L‐lactide‐co‐ε‐caprolactone) (6S‐PLCL) coating cross‐linked by hexamethylene diisocyanate (HDI) in different proportions. The coating causes an effective constraint on the movement of the monofilaments in the axial direction at the intersection. Due to this constraint, the coating enhanced mechanical properties of the stent and effectively reduced the axial elongation after crimping. Furthermore, the coated stent with the mass ratio of 5:1 (6S‐PLCL:HDI) showed the highest chronic outward force and the lowest axial elongation compared to the other mass ratios. The results can provide suggestions for improving the mechanical properties of polymer‐braided stents as compared to traditional metal stents.